Correlates of sun protection behaviors among melanoma survivors - Carolyn J. Heckman; Sharon L. Manne; Deborah A. Kashy; Trishnee Bhurosy; Lee Ritterband; Elliot J. Coups (BMC, 2021)
Abstract Background The study objective was to assess potential correlates of sun protection behaviors among melanoma survivors. Methods Participants were 441 melanoma survivors recruited from three health centers and a state cancer registry in the United States. Sun protection behaviors (sunscreen, shade, protective shirts, and hats) were assessed through an online survey, as were potential correlates (demographic, melanoma risk, knowledge and beliefs, psychological and social influence factors). Hierarchical multiple regression analyses were conducted. Results Correlates of sun protection behaviors included education, skin cancer risk factors, melanoma knowledge and beliefs, melanoma worry and distress, physician recommendation for sun protection, injunctive norms, and pro-protection beliefs (e.g., perceived barriers, self-efficacy). Conclusions Future efforts to improve sun safety among melanoma survivors may benefit from targeting individuals with lower education levels, and addressing sun protection social influence, barriers, and self-efficacy.